Cleopatra confesses - Meyer, Carolyn, 1935- (Simon & Schuster Books for Young Readers, 2012)
Princess Cleopatra, the third (and favorite) daughter of King Ptolemy XII, comes of age in ancient Egypt, accumulating power and discovering love.